Penerapan Model Project Based Learning untuk Meningkatkan Kerjasama dan Hasil Belajar Akidah Akhlak Siswa di Kelas XI MA Muhammadiyyah 1 Ponorogo - Winda Saputri; Zamzam Mustofa (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
Education plays a vital role in shaping character and developing individual potential, with the ability to collaborate being crucial in this global era. This study focuses on the low level of student collaboration and suboptimal Aqidah Akhlak learning outcomes at MA Muhammadiyah 1 Ponorogo, caused by a lack of innovative learning methods. Therefore, this study aims to examine the application of the Project-Based Learning method as a solution to improve student collaboration and learning outcomes. This study aims to: (1) describe the application of the Project-Based Learning method in teaching Aqidah Akhlak in class XI of MA Muhammadiyah 1 Ponorogo, (2) determine the impact of the Project-Based Learning method on student collaboration and learning outcomes, and (3) determine student perceptions of the application of the Project-Based Learning method in teaching Aqidah Akhlak. This study used a qualitative approach with descriptive methods. Data were collected through observation, interviews (with the principal, vice principal for curriculum, Aqidah Akhlak teacher, and class XI students), and documentation. The data analysis technique used was the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) the implementation of the Project Based Learning method is carried out through structured steps, encouraging active cooperation between teachers and students, with an emphasis on equal roles and responsibilities of each, (2) the Project Based Learning method has a positive impact on increasing collaboration, educational outcomes, and the development of students’ knowledge, attitudes, and skills as a whole, with changes in behavior that are seen in depth, (3) students have a positive view of the Project Based Learning method because it is considered more interesting, interactive, meaningful, and relevant to everyday life, which can be seen from increased motivation and active participation.